Assessing community engagement in the Standard Gauge Railway Project in Tanzania: A case study of the Morogoro – Makutupora Segment - Nyakega, Chacha Timasi; Tefurukwa, Oscar Whynijous (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2025)
Governments play a critical role in engaging communities in decision-making processes directly affecting their daily lives. Such engagement influences the feasibility and success of project implementation. However, the degree of community engagement varies across different projects. This study examines community engagement and perceptions regarding the implementation of the Standard Gauge Railway (SGR) project in Tanzania, focusing on Lot II, the Morogoro to Makutupora segment. The theoretical framework proposed by Fung guided the analysis. A qualitative approach was employed, with a sample of 30 respondents. Data were collected through focus group discussions (FGDs) and analyzed using content analysis. Findings indicate that community engagement in the SGR project occurred through the workforce provision, business activities supporting SGR workers, protection of properties and personnel, and land allocation. It enhances project implementation by fostering a sense of local ownership and promoting efficiency and sustainability. This study highlights the importance of sustaining community engagement in projects of any scale to ensure inclusive and sustainable development. These findings offer valuable insights for policymakers and project planners and align with the Sustainable Development Goals (SDGs) on industrialization and infrastructure.